Serum Magnesium Level Is Associated with Type 2 Diabetes in Women with a History of Gestational Diabetes Mellitus: The Korea National Diabetes Program Study - Yang, Sae Jeong; Hwang, Soon Young; Baik, Sei Hyun; Lee, Kwan Woo; Nam, Moon Suk; Park, Yong Soo; Woo, Jeong Taek; Kim, Young Seol; Park, Sunmin; Park, So-Young; Yim, Chang Hoon; Yoon, Hyun Koo; et al. (Journal of Korean medical science, 2014)
Gestational diabetes mellitus (GDM) is a strong predictor of postpartum prediabetes and transition to overt type 2 diabetes (T2DM). Although many reports indicate that low magnesium is correlated with deteriorated glucose tolerance, the association between postpartum serum magnesium level and the risk for T2DM in women with a history of GDM has not been evaluated. We analyzed postpartum serum magnesium levels and development of prediabetes and T2DM in women with prior GDM according to American Diabetes Association (ADA) criteria using the Korean National Diabetes Program (KNDP) GDM cohort. During a mean follow-up of 15.6 ± 2.0 months after screening, 116 women were divided into three groups according to glucose tolerance status. Ultimately, eight patients (6.9%) were diagnosed with T2DM, 59 patients (50.9%) with prediabetes, and 49 patients (42.2%) with normal glucose tolerance (NGT) after follow-up. The T2DM group had the lowest serum magnesium level (0.65 [0.63-0.68] mM/L) in the postpartum period, but there was no significant difference between the prediabetes group (0.70 [0.65-0.70] mM/L) and the NGT group (0.70 [0.65-0.70] mM/L) (P=0.073) Multiple logistic regression analysis showed that postpartum HOMA-IR was a significant predictor of both prediabetes and T2DM. Moreover, we found that postpartum serum magnesium level was also a possible predictor for T2DM development. Serum magnesium level in the postpartum period may be a possible predictor for T2DM development in women with a history of GDM.